Economic returns and risks to investment in education: An application of the multifactor CAPM - Antonios Athanassiadis (International Journal of Economic Sciences and Applied Research, 2011)
Considering the investment in education as uncertain financial decision making we modify the short-cut method of calculating rates of return to education by incorporating the risk premium. Recognizing that market risk isn't the only factor affecting returns, we estimate the returns to education in fifteen member - states of the European Union and the Organisation for Economic Co-operation and Development during the period 2005 2007 as seen from a macroeconomic point of view using Multifactor CAPM. Following this model we assess, except market risk, the impact of three key macroeconomic variables (investments, productivity and unemployment) on returns and, using panel data regression techniques, we investigate whether this holds true with respect to investment in education. We also evaluate the risk - adjusted performance of investment in education and the role of returns as well as that of the key macroeconomic variables to economic development. The results tend to confirm the theoretical expectations and empirical literature. The purpose of the present study is twofold: first, to estimate the relationship between education returns and risk and second to measure the impact of return and key macro factors on real GDP growth rate, therefore casting light in the channels through which the economicgrowth can be affected.
Keywords: I22; G11; C23; 330; CAPM; human capital theory; GMM